2017
DOI: 10.3791/56014
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Amyloid-β42 Toxicity and Neurodegeneration in Adult Zebrafish Brain

Abstract: Alzheimer's disease (AD) is a debilitating neurodegenerative disease in which accumulation of toxic amyloid-β42 (Aβ42) peptides leads to synaptic degeneration, inflammation, neuronal death, and learning deficits. Humans cannot regenerate lost neurons in the case of AD in part due to impaired proliferative capacity of the neural stem/progenitor cells (NSPCs) and reduced neurogenesis. Therefore, efficient regenerative therapies should also enhance the proliferation and neurogenic capacity of NSPCs. Zebrafish (Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 50 publications
2
39
0
Order By: Relevance
“…Since Aβ42/IL4 enhances neural stem cell (NSC) proliferation in adult zebrafish brain (Bhattarai et al, 2017a;Bhattarai et al, 2016;Bhattarai et al, 2017b;Kizil, 2018;Kizil and Bhattarai, 2018b) and they downregulate 5-HT ( Figure 1E,F), we hypothesized that 5-HT could be negatively affecting NSC plasticity. To test this, we injected 5-HT into adult zebrafish brain and analyzed the proliferation of NSCs (S100b/PCNA double positive cells) (Figure 2A-C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since Aβ42/IL4 enhances neural stem cell (NSC) proliferation in adult zebrafish brain (Bhattarai et al, 2017a;Bhattarai et al, 2016;Bhattarai et al, 2017b;Kizil, 2018;Kizil and Bhattarai, 2018b) and they downregulate 5-HT ( Figure 1E,F), we hypothesized that 5-HT could be negatively affecting NSC plasticity. To test this, we injected 5-HT into adult zebrafish brain and analyzed the proliferation of NSCs (S100b/PCNA double positive cells) (Figure 2A-C).…”
Section: Resultsmentioning
confidence: 99%
“…Amyloid-β42 (Aβ42) synthesis was performed as described . Cerebroventricular microinjection in adult zebrafish brain were performed as previously described (Bhattarai et al, 2017a;Bhattarai et al, 2016;Bhattarai et al, 2017b). PBS (1μl), Aβ42 (1 μl, 20 μM), IL4 (1 μl, 10 μg/ml), BDNF (1 μl, 100ng/ml), 5-HT (1 μl, 100 μM), ngfra morpholino (1μl, 10uM) were injected.…”
Section: Peptide Synthesis Cerebroventricular Microinjection In Adulmentioning
confidence: 99%
See 1 more Smart Citation
“…Its direct effect on neuronal integrity and stem cell plasticity, and whether it is the causative agent for Alzheimer’s pathology are still controversial. We previously showed that Aβ42 treatment causes phenotypes reminiscent of human AD conditions, namely, cell death, synaptic degeneration, inflammation and cognitive deficits (Bhattarai et al, 2017a; Bhattarai et al, 2016b; Bhattarai et al, 2017b). However, in contrast to mammals, zebrafish NSPCs increased their proliferation and neurogenic output indicating that adult zebrafish brain responds to Aβ42 toxicity by enhancing NSPC plasticity and neuroregeneration (Bhattarai et al, 2016b; Bhattarai et al, 2017b).…”
Section: Resultsmentioning
confidence: 99%
“…Central nervous system regeneration is catching particular attention because of robust neural regeneration ability in zebrafish and clinical ramifications it might bring, which could not be possible to elucidate with mammalian models. For instance, we have recently generated an Amyloid toxicity model in adult zebrafish brain and identified that zebrafish can effectively enhance its neural stem cell proliferation and neurogenesis with key activity of Interleukin-4 (IL4) that mediates the crosstalk between disease pathology in neurons and initiation of regenerative output in stem cells (Bhattarai et al, 2017a; Bhattarai et al, 2016b; Bhattarai et al, 2017b; Kizil, 2018). We also found that IL4 can directly affect the human neural stem cells in a similar fashion to induce the proliferative and neurogenic ability (Papadimitriou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%